Literature Study: The Convergence of IFRS (International Financial Reporting Standard) to Ensure Full Compliance in Reporting The Financial Statement - Siregar, Yentina (JOURNAL OF ECONOMIC SCIENCE, 2015)
The adoption of IFRS around the globe has stimulated empirical research that investigates the financial reporting and capital market effects associated with an accounting regime change. These studies differ in their analysis period, jurisdictional setting, and research design, and they report varying findings. We conduct a meta-analysis of IFRS adoption studies investigating financial reporting effects, namely value relevance and earnings transparency in the form of discretionary accruals, as well as capital market effects, specifically the quality of analysts earnings forecasts.We investigate whether the adoption of International Financial Reporting Standards (IFRS) in SAK and GAAP to compliance in the Financial Statements. The samples of this study are 40 banking industries listed in BEI in 2009-2012. By purposive sampling are 26 banking industries for one period so that are 104 samples as the catagories of mandatory and voluntary disclosure. This study is to evaluate convergence of firms accounting practices from three perspectives: (1) harmonization, (2) adaptation, (3) adoption. However, these associations are moderated by the model used for empirical investigation of value relevance and discretionary accrual effects; they are also moderated by the adoption being voluntary or mandatory. The result t value is 1.328 and t table is 2.039 (t value is Î±= 5%: 2 = 2,5 % (two tailed tested), so that t value < t table (1,328<2,039), Null Hyphotesis was accepted that is significant effects positively of IFRS convergence to ensure full compliance in reporting the financial statement. R2 (R Square) is 0.790 or (79%). This study explained the effect of IFRS convergence to compliance in reporting the financial statement is 79% or the variety of independent variable in this model (IFRS convergence) explained dependent variable (compliance in reporting the financial statement) is 79%, and 21% is effected by other variables not included in this model.